International Monetary Fund Annual Report 1974. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1974)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1974. The report highlights that in mid-1974, the world economy was in the throes of a virulent and widespread inflation, a deceleration of economic growth in reaction to the preceding high rate of expansion, and a massive disequilibrium in international payments. The average annual rate of inflation in industrial countries, already 7 percent in 1973, reached 12 percent (in terms of gross national product deflators) in the first half of 1974.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet